Institutionalized Rent-Seeking: The Case of Sugar Imports at the Indonesia-Malaysia Land Border - Benediktus Hendro; Agustinus Subarsono; Gabriel Lele; Ratminto Ratminto (Universitas Teuku Umar, 2023)
This article explored the rent-seeking phenomenon in sugar imports at the Indonesia-Malaysia land border. The rent-seeking phenomenon in sugar imports involves many actors interested in importing sugar for business purposes. This study is intriguing because interest actors conduct rent-seeking through regulatory loopholes controlled by the bureaucracy on the border of the two countries. Therefore, this study focused on the actor's strategy to realise sugar imports through rent-seeking practices. This article applied the Rational Choice Institutionalism (RCI) theory as an analytical framework. Using a qualitative phenomenological approach in data collection, this article found that sugar imports for business purposes involve two networks of interest groups, namely communal networks and associational networks. These interest group networks import sugar for business purposes through rent-seeking practices. As a form of actor's choice of action, rent-seeking is a strategy in responding to obstacles and incentives from formal institutions to maximise profits from the reality of the gap in the sugar trade at the border. The variations in the strategies of interest actors in the two sugar import periods (2011-2014 and 2015-2018) have shown that rent-seeking is a form of a rational choice institution created within an institutional framework. This investigation suggests a review of the formal institutional structure, which is the rule of the game in sugar imports because reality demonstrates that formal institutional structures can become an arena of rent-seeking that interest actors exploit